Strategi Kolaborasi Uniqlo dengan Program Anime terhadap Hasil Penjualan: Studi pada Uniqlo dengan Program Anime - Muttaqin, Zaenal; Savitri, Citra; Suroso, Suroso; Gu, Kan Myon (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to reveal the collaboration strategy between Uniqlo and anime programs on sales results. The research method used is to use a qualitative approach to understand more deeply about the patterns, trends, or phenomena involved to explore and understand the more subjective and complex aspects of the data in the sales data table. The focus of the study involves various articles related to Uniqlo's management strategy, as well as discussing in general Uniqlo's collaboration strategy with anime programs, and developments in market size, share, and trends in the anime industry that have been previously published. The literature is carefully analyzed and then compiled and presented.